2020
DOI: 10.18502/ijrm.v13i10.7768
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine reduces the negative effects of formalin on sperm parameters, chromatin condensation and apoptosis in mice: An experimental study

Abstract: Background: Formalin is commonly applied as an antiseptic and tissue fixative. It has reactive molecules that lead to its cytotoxic effects. According to recent studies, formalin causes a change in the testicular and sperm structure and L-carnitine (LC) acts as an antioxidant to counteract its effects. Objectives: This study aimed to investigate the protective effects of LC on the parameters, chromatin condensation and apoptosis of mice sperm exposed to formalin. Materials and Methods: In this expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, L-carnitine with meliorates TAC (Ghanbarzadeh et al, 2014) and scavenges free radicals such as ROS (Galarza et al, 2020;Jiang et al, 2020;Nery et al, 2020) can prevent oxidative stress and pursuant apoptosis induction (Jiang et al, 2020;Lee & Park, 2016). Many studies have reported a reduction in DNA fragmentation of spermatozoa through TUNEL (Ezati et al, 2020) and SCD (Abad et al, 2013) methods by prescribing this antioxidant.…”
Section: Sperm Viability Assaymentioning
confidence: 99%
“…In addition, L-carnitine with meliorates TAC (Ghanbarzadeh et al, 2014) and scavenges free radicals such as ROS (Galarza et al, 2020;Jiang et al, 2020;Nery et al, 2020) can prevent oxidative stress and pursuant apoptosis induction (Jiang et al, 2020;Lee & Park, 2016). Many studies have reported a reduction in DNA fragmentation of spermatozoa through TUNEL (Ezati et al, 2020) and SCD (Abad et al, 2013) methods by prescribing this antioxidant.…”
Section: Sperm Viability Assaymentioning
confidence: 99%
“…Carnitine is an amino acid and is found to be in high concentrations throughout the structure of the testes and the epididymis and the spermatozoa [108]. Carnitine is involved in a wide range of physiological processes, thought to play many important functions in semen cells including maturation of the sperm [109], initiation of motility [110] and protecting sperm chromatin from oxidative damage [111,112]. Carnitine has been studied extensively for the impact on semen and fertility parameters, predominantly in those diagnosed with idiopathic oligoasthenozoospermia [113].…”
Section: L-carnitinementioning
confidence: 99%